SIX THINKING HATS STRATEGY TO THE EIGHTH GRADE STUDENTS OF PGRI JUNIOR HIGH SCHOOL 9 OF PALEMBANG - Tahrun Tahrun; Noviati Noviati (Universitas PGRI Palembang, 2020)
The problem of this study was â€œWas it effective to use Six Thinking Hats Strategy in teaching reading narrative text to the eighth grade students of PGRI Junior High School 9 of Palembang?â€ The aim of this study was to find out whether or not it was effective to use Six Thinking Hats strategy in teaching reading narrative text to the eighth grade students of PGRI Junior High School 9 of Palembang.The population was the eighth grade students of PGRI Junior High School 9 of Palembang in academic year of 2018/2019. The sample was 36 students who were chosen by cluster random sampling. This study employed Pre- experimental design with the one-group pretest-posttest design. The data were collected through written test in form of Multiple choice which implemented in pre-test and post-test. The data were analyzed by using matched t-test formula.The result of the study is found that the studentsâ€™ average score in theÂ Â Â Â Â Â Â Â pre-test was 47,57 and the studentsâ€™ average score in the post-test was 73,68. Based on the matched t-test calculation, it was found that the t-obtained was 4,854. The critical value of 5% significance level was 1.690. It showed that theÂ Â Â Â Â t-obtained was higher than the t-table. From this study it was found that teaching reading narrative text by using Six Thinking Hats strategy to the eighth grade students of PGRI Junior High School 9 of Palembang was effective.